City of saviors - Hall, Rachel Howzell (Hall, Rachel Howzell. Detective Elouise Norton novel., 2017)
After a long Labor Day weekend, seventy-three-year-old Eugene Washington is found dead in his Leimert Park home. At first blush, his death seems unremarkable<U+2014>heatwave combined with food poisoning from a holiday barbecue. But something in the way Washington died doesn<U+2019>t make sense. LAPD Homicide Detective Elouise "Lou" Norton is called to investigate the death and learns that the only family Washington had was the 6,000-member congregation of Blessed Mission Ministries, led by Bishop Solomon Tate. But something wicked is lurking among the congregants of this church. Lou<U+2019>s partner, Detective Colin Taggert, thinks her focus on the congregation comes from her distrust of organized religion. But Lou is convinced that the murderer is sitting in one of those red velvet pews<U+2014>and that Bishop Tate may be protecting the wolf in the flock. Lou must force the truth into the light and confront her own demons in order to save another soul before it<U+2019>s too late.